2011
DOI: 10.1089/scd.2010.0353
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotency Regulators in Human Mesenchymal Stem Cells: Expression of NANOG But Not of OCT-4 and SOX-2

Abstract: Mesenchymal stem cells (MSCs) are adult multipotent cells able to differentiate toward mature mesodermal lineages. In spite of more than a decade of investigation, little is known about the molecular mechanisms regulating the undifferentiated state and the identity of distinct functional subpopulations in these cells. Transcription factors that regulate the maintenance of the pluripotent state in embryonic stem cells, including NANOG, SOX2, and OCT4, have been proposed to play a similar role also in adult stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
93
3
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 46 publications
16
93
3
4
Order By: Relevance
“…In contrast, characterization of pluripotent markers in both untreated MSCs and 5-FU-MSCs showed expression of Nanog but not Oct-3/4. This is in agreement with past reports that MSCs express Nanog but not Oct-3/4 (16,30).…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, characterization of pluripotent markers in both untreated MSCs and 5-FU-MSCs showed expression of Nanog but not Oct-3/4. This is in agreement with past reports that MSCs express Nanog but not Oct-3/4 (16,30).…”
Section: Discussionsupporting
confidence: 94%
“…The lack of expression of these pluripotency markers in intact patellar tendon suggested that immunohistochemical staining of these markers was not suitable for the detection of tendon stem cell in intact tendon in situ. The activation of Oct4, Nanog, Sox2, and nucleostemin as well as CD146 after tendon injury might be related to the functions of these proteins in regulating self-renewal, cell proliferation, differentiation, and/or angiogenesis [28][29][30][31][32].…”
Section: Role Of Lrcs During Tendon Repairmentioning
confidence: 99%
“…TDSCs expressed Nanog, Oct4, Sox2, and nucleostemin that were not observed in LRCs in intact tendon in vivo. The isolation of LRCs induced trauma to tendon, and this might trigger processes similar to tendon injury [28]. The expression of pluripotency markers and pericyte-related markers after …”
Section: Most Tdscs Are Lrcs and Activation Of Lrcs After Isolationmentioning
confidence: 99%
“…Such a surprising high plasticity of MSCs might be explained by the expression of a variety of gene families in undifferentiated MSCs. Several recent studies have shown that MSCs express several embryonic stem cell markers (pluripotent markers) such as Oct4, Nanog, alkaline phosphatase and SSEA-4, and SOX2 (Park & Patel, 2010;Pierantozzi et al, 2011;Riekstina et al, 2009). It also has been demonstrated that the translational and transcriptional machinery in MSCs responsible for the expression of multiple genes typical of several derivatives of three germ layers are not silenced, rather operating at the low level (Blondheim et al, 2006;Tondreau et al, 2008).…”
Section: Mesenchymal Stem Cells As An Ideal Source Of Cells For Regenmentioning
confidence: 99%